Efficient Semantics-Based Compliance Checking Using LTL Formulae and Unfolding - Liang Song; Jianmin Wang; Lijie Wen; Hui Kong (Journal of Applied Mathematics, 2013)
Business process models are required to be in line with frequently changing regulations, policies, and environments. In the field of intelligent modeling, organisations concern automated business process compliance checking as the manual verification is a time-consuming and inefficient work. There exist two key issues for business process compliance checking. One is the definition of a business process retrieval language that can be employed to capture the compliance rules, the other concerns efficient evaluation of these rules. Traditional syntax-based retrieval approaches cannot deal with various important requirements of compliance checking in practice. Although a retrieval language that is based on semantics can overcome the drawback of syntax-based ones, it suffers from the well-known state space explosion. In this paper, we define a semantics-based process model query language through simplifying a property specification pattern system without affecting its expressiveness. We use this language to capture semantics-based compliance rules and constraints. We also propose a feasible approach in such a way that the compliance checking will not suffer from the state space explosion as much as possible. A tool is implemented to evaluate the efficiency. An experiment conducted on three model collections illustrates that our technology is very efficient.